Pre-licensure examination as predictor of licensure examination for teachers result - Rainer R. Fiscal; Adriel G. Roman (Institute of Advanced Engineering and Science, 2022)
Licensure examination for teachers (LET) is the major requirement of teachers in the Philippines before practicing teaching profession. As such, it is imperative to monitor necessary parameters to increase passing percentage of teachers in LET. This study attempted to examine the relationship between performance in pre-LET and LET of 71 elementary education (BEEd) and 127 secondary education (BSEd) graduates in one university in the Philippines. Individual and aggregated data were secured from the college of teacher education dean’s office and Professional regulations commission (PRC). Using the descriptive-correlation method of research, this study presented the null hypothesis that pre-licensure is not a predictor of LET results. Findings showed that there is a notable relationship between the pre-LET and LET examination performances. Using linear regression analysis, ratings attained by the graduates in pre-LET can predict the performance in LET with higher level of confidence. The study confirmed that for general education (GenEd) and professional education components of licensure examination for BEEd, the pre-LET scores of education graduates are significant predictors.